EFFECT OF MALARIA PARASITAEMIA AND HAEMATOLOGICAL PARAMETERS IN PATIENTS ATTENDING SELECTED HOSPITALS IN GOMBE STATE, NIGERIA - J, PHILIMON; G, CHESSED; PUKUMA; E, ABBA; Y.U, AMINA; M., ISHAKU; Y, LAMOGO; A., JEMIMAH; A., SARKI; A. A., MUHAMMAD; S, SHUAIBU; A, FATAI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Malaria is a major public health problem in most countries of the tropics and sub tropics. Malarial parasitemia causes wide ranging hematological and Biochemical alterations and may lead to life threatening complications if not diagnosed and treated in time. The aim of the study is to observe effects of Parasitemia on blood indices and liver function among patients attending six (6) selected hospitals in Gombe State, Nigeria. A total of 2400 patients attending the outpatient department of the six (6) selected hospitals were enrolled as test subjects. Venus blood was collected. Malaria parasite density was determined in various blood smears and analyzed for blood indices- Hb, PCV, total WBC, RBC, platelets. A total of 2400 individuals were investigated in this study. Out of the total number of study subjects from the six(6) randomly selected hospitals in Gombe state, 1799(74.9%) were positive for malaria parasite while 601(25.0%) were negative, the difference in prevalence was significant (p<0.05). Out of the 2400 individuals examined, 726(60.5%) were males while 1073(89.4%) were females, the difference in prevalence was significant (p <0.05). Prevalence in relation to age showed that <18 years had the highest prevalence 1001(41.7%) while age range above >40 years had the least prevalence of 106(4.4%) However, the differences between the age groups were statistically significant (p<0.001). Among the 1,799 malaria positive individuals, 1,122 (62.4%) had mild + infection, while 143(7.9%) had severe +++ infection. This is statistically significance at (p<0.05). According to sex, 440(60.9%), 203(27.1%) and 63(8.7%) males had mild +, moderate ++ and severe +++ infection respectively. On the other hand, 682(63.5%), 311(28.1%) and 80(7.5%) females had mild +, moderate ++ and severe +++ infection respectively, (p<0.05). Among the age groups, <18 years, had only mild + infection 599(59.8%), 296(29.6%) moderate ++ infection and 106(10.6%) severe +++ infection. Among the age group >40years, 63(59.4%) had mild infection, 27(25.5%) had moderate infection while, 16(15.0%) had severe infection. The differences in prevalence was statistically significant (p<0.05). Haematological parameters revealed that, the levels of PCV (27.9±4.09%), Hb (8.09±0.16g/dL), TWBCs (3.24±2.8/µl), RBC (2.71± 0.98 µl) and platelets (102.6±7.09 µl) showed significant (p<0.05) decrease, malaria infected patients compared to the uninfected patients. According to age, <18years had decrease in haematological values compared to 18-40years and >40years. In relation to sex, there was also a significant decrease in haematological parameters (p<0.05) in females compared to males.